What are The Sensitivity, Specificity, and Positive Predictive Value of Ultrasound for Diagnosing Acute Appendicitis in Pediatric Patients? : A Systematic Review - M. Faza Akroma; Ade Nur Imansyah (The Indonesian Journal of General Medicine, 2026)
Background: Acute appendicitis is the most common pediatric surgical emergency, yet its diagnosis remains challenging due to atypical presentations and radiation concerns with computed tomography (CT). Ultrasound (US) is recommended as the first-line imaging modality, but published diagnostic accuracy varies considerably across studies and clinical settings. Methods: This systematic review synthesized data from 80 studies examining the diagnostic accuracy of US for acute appendicitis in pediatric patients (aged ≤18 years). We extracted data on study characteristics, US methodology, reference standards (histopathology, surgery, clinical follow-up), diagnostic accuracy metrics (sensitivity, specificity, predictive values), appendix visualization rates, operator experience, and performance modifiers. Results: Pooled estimates from high-quality meta-analyses demonstrated that conventional US has a sensitivity of 88–93% and specificity of 89–94% for pediatric appendicitis (2,3). However, individual studies showed extreme variability: sensitivity ranged from 16% to 99.6% and specificity from 68% to 100% (1,6,7). Point-of-care US (POCUS) performed by emergency physicians had lower pooled sensitivity (78–86%) but maintained high specificity (~90%) (8,10). Appendix visualization rates varied dramatically from 36% to 91%, with non-diagnostic scan rates of 11–63% (1,14,16). For perforated appendicitis, US demonstrated low sensitivity (23–44%) despite high specificity (90–100%) (11,12,45). Obesity significantly increased the odds of equivocal scans (OR 1.86, 95% CI: 1.28–2.70) (17), and after-hour scanning reduced visualization success (P<0.001) (18). Staged imaging protocols combining US with selective CT or MRI achieved high accuracy while reducing radiation exposure (4,5,19,20). When combined with clinical scoring systems (Pediatric Appendicitis Score ≥4), US sensitivity increased to 96.2% and specificity to 94.1% (51). Discussion: Ultrasound diagnostic accuracy for pediatric appendicitis is highly context-dependent. Excellent performance (sensitivity >90%, specificity >90%) is achievable under optimal conditions: trained pediatric-focused operators, high-volume tertiary centers, favorable patient factors, and integration into staged diagnostic algorithms. However, performance degrades predictably in community hospitals without pediatric specialization, obese patients, complex anatomy (retrocecal or pelvic appendix), after-hours studies, and cases of perforated appendicitis. Secondary inflammatory signs (echogenic fat, periappendiceal fluid, hyperemia, appendicoliths) improve diagnostic certainty when the appendix is not fully visualized (39,41,44). The negative predictive value of a non-visualized appendix in low-risk patients approaches 98–99%, allowing safe discharge (14,38,69). Ultrasound remains comparable to CT and MRI when optimally performed, with the advantage of no ionizing radiation (2,53). Radiation-free pathways using US followed by selective MRI achieve outcomes equivalent to CT-based protocols (20,27). Conclusion: Ultrasound is a valuable first-line imaging modality for pediatric appendicitis, with excellent performance in experienced hands and appropriate settings. Its main limitations are operator dependence, low sensitivity for perforated appendicitis, and high non-visualization rates in obese or younger children. We recommend: (1) structured training programs for operators, (2) standardized reporting templates, (3) integration with clinical scoring systems, (4) staged imaging protocols with selective CT or MRI for equivocal cases, and (5) quality assurance programs, especially in community hospitals.